Impact of chronic blockade of adenosine A2A receptors on neurobehavioral changes induced by intermittent ethanol exposure in adolescent female rats - focus on the prefrontal cortex - Santos, Joana Martins Duarte (2022)
Dissertação de Mestrado em Biologia Celular e Molecular apresentada à Faculdade de Ciências e Tecnologia